DNA/RNA metabarcoding and morphological analysis of epipelagic copepod communities in the Izu Ridge off the southern coast of Japan. (24th May 2021) - Hirai, Junya; Hidaka, Kiyotaka; Nagai, Satoshi; Shimizu, Yugo
Abstract: The Izu Ridge off the southern coast of Japan is composed of many seamounts and knolls and is an important fishery ground and hatchery for commercially important fish. As pelagic copepods link lower and higher trophic levels, we investigated the epipelagic copepods in the Izu Ridge using 28S DNA/RNA metabarcoding and microscopic approaches. In comparison with off-ridge regions, a low water temperature and high chlorophyll a concentration were observed in the Izu Ridge, possibly attributed to high levels of nutrients supplied by strong turbulences around the complex topography. We observed unique copepod communities with a large total biomass in the Izu Ridge, owing to the increased dominance of large copepod species. rRNA:rDNA (28S ratio) of these large species mainly showed positive correlations with the chlorophyll a concentration, suggesting a rapid response to the food supply. Migrating copepods were less dominant around the Izu Ridge with a shallow water depth. Higher species diversity and more rare species were detected in the Izu Ridge, which might be maintained by complex environment conditions including temporal and spatial variations in the concentration of chlorophyll a . Thus, the combined approach characterized copepod community structure and diversity supporting the rich pelagic ecosystems in the Izu Ridge.